2017
DOI: 10.1108/cdi-01-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

The challenges of employee resourcing: the perceptions of managers in Nigeria

Abstract: The Challenges of Employee Resourcing: The Perceptions of Managers in NigeriaPurpose -The existing literature on the recruitment and selection process in Sub-Saharan African (SSA) context has not sufficiently revealed inherent challenges. This article examines managers' perceptions of employee resourcing in Nigeria.Methodology -This article uses qualitative data which was generated from the semistructured interviews of 61 managers across the six geo-political zones of Nigeria.Findings -The article finds that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Although ethnicity is a common theme in the diversity management literature (Collier, 2019), it is rarely explored in relation to SHRM in emerging economies. The extant literature shows that ethnicity features in areas of HR delivery including employee resourcing, identity construction, ethnic framing, and career development (Adisa et al, 2017;Arifeen & Syed, 2019). This study demonstrates that ethnicity engenders the moral behaviour required for the nexus through the development of controls based on fairness and transparency, which influence the moral behaviours necessary for the CS-HRMP nexus in emerging economies.…”
Section: Discussionmentioning
confidence: 99%
“…Although ethnicity is a common theme in the diversity management literature (Collier, 2019), it is rarely explored in relation to SHRM in emerging economies. The extant literature shows that ethnicity features in areas of HR delivery including employee resourcing, identity construction, ethnic framing, and career development (Adisa et al, 2017;Arifeen & Syed, 2019). This study demonstrates that ethnicity engenders the moral behaviour required for the nexus through the development of controls based on fairness and transparency, which influence the moral behaviours necessary for the CS-HRMP nexus in emerging economies.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly so, employee resourcing strategies, such as workforce planning and succession planning, have remained a grey area in small restaurant business research. While there is convergence of literature on the contribution of environmental factors such as manager's expertise and experience, institutional support, quality of human resources, economic growth, corruption and political stability to leveraging the adoption of effective employee resourcing strategies (Adisa et al, 2017;Česynienė, Diskienė, & Stankevičienė, 2013;Ogunyomi & Bruning, 2016;Punia & Sharma, 2015) and the value of environmental influences in heightening business performance (Kraja & Osmania, 2015;Njuguna-Kinyua et al, 2014), there is limited research that explores the interplay among environmental influences, employee resourcing strategies and performance of small restaurant businesses in a developing context. Actually, literature search has revealed that there is a paucity of literature that explores whether a relationship exists between environmental influences, employee resourcing practices and SME performance.…”
Section: Problem Statementmentioning
confidence: 99%
“…In a recent study, Adisa, Osabutey, Gbadamosi and Mordi [48] found that quota system policies adversely impacted recruitment and selection in Nigeria. While quota system is a good practice in that it provides equity and fairness in a highly diverse society like Nigeria, it defies the merit principle (i.e.…”
Section: Regulatory Institutional Factorsmentioning
confidence: 99%